Comparative study of two deleted Mycobacterium bovis strains in experimental animal models - Ferrara Muñiz, Ximena; Blanco, Federico Carlos; Garcia, Elizabeth Andrea; Delgado, Fernando Oscar; Marfil, Maria Jimena; Zumarraga, Martin Jose; Cataldi, Angel Adrian; Eirin, Maria Emilia (European Society of Mycobacteriology, 2024)
Poster